Tinular: Learning from Kemujan's Living Knowledge System - Wanda Aulia Rahma (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2026)
Abstract Tinular is a learning facility that views the coastal community and landscape of Kemujan as a living library, where traditional knowledge is continuously practiced, shared, and passed down across generations. Through experiential, community-based, and project-based learning, learners engage directly with local communities and the coastal environment in which this knowledge has evolved. By positioning people, place, and everyday practices as sources of learning, the facility creates opportunities for knowledge exchange while supporting the preservation and continuation of Kemujan's living knowledge system.